Dynamics of dust clouds in plasmas - Kravchenko, O.Yu.; Yurchuk, M.M.; Radchenko, O.M. (Вопросы атомной науки и техники, 2007)
We study a dynamics of dust clouds embedded in the infinite uniform initially plasma using computer simulation. In the one dimension, the movement of dust particles and ions is governed by cold hydrodynamics equations, electrons are assumed to be in thermal equilibrium. It is assumed that the forces on the dust consist of electrostatic force and ion drag forces. The spatial distributions of parameters were obtained at various initial densities of dust grains at different times. Results show the expansion of dust clouds at low initial dust grain density, which is evidence of exceeding the electrostatic force over the ion drag force. At the increasing of dust density oscillations of the central part of dust cloud are observed. За допомогою комп’ютерного моделювання досліджується динаміка пилових згустків в необмеженій плазмі. Рух пилових частинок та іонів описується одновимірними рівняннями холодної гідродинаміки, електрони вважаються рівноважними. В моделі припускається, що на пилові частинки діють електростатична сила та сила іонного тертя. Одержані просторові розподіли параметрів в різні моменти часу при різних значеннях початкової концентрації пилинок. Показано, що пилові згустки розширюються при малих концентраціях пилових частинок, оскільки в цьому випадку електростатична сила переважає силу іонного тертя. При збільшенні концентрації пилових частинок спостерігаються осциляції центральної частини пилових згустків. При помощи компьютерного моделирования исследуется динамика пылевых сгустков в неограниченной плазме. Движение пылевых частиц и ионов описывается одномерными уравнениями холодной гидродинамики, электроны предполагаются равновесными. В модели предполагается, что на пылевые частицы действуют электростатическая сила и сила ионного трения. Получены пространственные распределения параметров в различные моменты времени при различных значениях начальной концентрации пылинок. Показано, что пылевые сгустки расширяются при малых концентрациях пылевых частиц, поскольку в этом случае электростатическая сила превышает силу ионного трения. При увеличении концентрации пылевых частиц наблюдаются осцилляции центральной части пылевых сгустков.